Development of Miconazole-Loaded Microemulsions for Enhanced Topical Delivery and Non-Destructive Analysis by Near-Infrared Spectroscopy - Chutima Phechkrajang; Wichuda Phiphitphibunsuk; Rapee Sukthongchaikool; Nantana Nuchtavorn; Jiraporn Leanpolchareanchai (MDPI AG, 2023)
The antifungal drug miconazole nitrate has a low solubility in water, leading to reduced therapeutic efficacy. To address this limitation, miconazole-loaded microemulsions were developed and assessed for topical skin delivery, prepared through spontaneous emulsification with oleic acid and water. The surfactant phase included a mixture of polyoxyethylene sorbitan monooleate (PSM) and various cosurfactants (ethanol, 2-(2-ethoxyethoxy) ethanol, or 2-propanol). The optimal miconazole-loaded microemulsion containing PSM and ethanol at a ratio of 1:1 showed a mean cumulative drug permeation of 87.6 ± 5.8 μg/cm2 across pig skin. The formulation exhibited higher cumulative permeation, permeation flux, and drug deposition than conventional cream and significantly increased the in vitro inhibition of Candida albicans compared with cream (p < 0.05). Over the course of a 3-month study conducted at a temperature of 30 ± 2 °C, the microemulsion exhibited favorable physicochemical stability. This outcome signifies its potential suitability as a carrier for effectively administering miconazole through topical administration. Additionally, a non-destructive technique employing near-infrared spectroscopy coupled with a partial least-squares regression (PLSR) model was developed to quantitatively analyze microemulsions containing miconazole nitrate. This approach eliminates the need for sample preparation. The optimal PLSR model was derived by utilizing orthogonal signal correction pretreated data with one latent factor. This model exhibited a remarkable R2 value of 0.9919 and a root mean square error of calibration of 0.0488. Consequently, this methodology holds potential for effectively monitoring the quantity of miconazole nitrate in various formulations, including both conventional and innovative ones.